Meningkatkan Motivasi Belajar Siswa Melalui Bimbingan Kelompok dengan Teknik Problem Solving dimasa Pandemi Covid-19 - Ni Luh Idayanti; Nurlela Nurlela; Muhammad Ferdiansyah; Arizona Arizona (Kuras Institute, 2022)
The problem examined in this study was the low motivation of student learning during the Pandemi Covid - 19 at SMP Negeri 2 Palembang. The goal to be achieved in this study is to find out whether group guidance services with problem solving techniques can increase student motivation in the era of Pandemi Covid - 19 at SMP Negeri 2 Palembang. From the results of research and data analysis shows that there is an increase in student learning motivation after the provision of group guidance services with problem solving techniques is evidenced by the results of the Wilcoxon test with Zhitung > Ztabel values ​​of 2,677 > 2,007, then HA is accepted and Ho is rejected. This means that there is an increase between pre-test and post-test values, so it can be concluded that group guidance with problem solving techniques can increase student learning motivation in Pandemi Covid-19 in SMP Negeri 2 Palembang.